Infância, TIC e brincadeiras: um estudo na visão de profissionais da educação infantil: desafios da geração Homo zapiens - Canassa, Luciana Maria Rinaldini (2013)
This thesis aims to analyze the role of play and games in the context of early childhood education and how does the media influence and media in children s play; tensed verify the actions of teachers and management team on the possible influence of ICT on the behavior of children aged 4-6 years, both electronic games, such as media characters. Given the infancy of the digital era, sporting, thinks and acts in direct contact with ICT, justified the need for this research, based on Kamii Moyles and on the stages of human development and the importance of play for children full training. The research adopted procedures and qualitative case study design as for being an approach that can substantiate the situations experienced within the Institution of Child Education. Survey participants were the director and coordinator of school and four teachers Childhood Education network of the Municipality of the City of Birigüi-SP. Data interpretation was developed through content analysis. The survey conducted showed that ICTs are part of everyday life for children, since children participate less of traditional sports and games in school and are more interested in handling electronic devices such as games, phones, internet and also watch TV at home. The teachers recognized the importance of play, however, that reputation was assigned only in discourse, because we did not observe the actual practice within the speeches collected through interviews. We found that the teacher lacks solid theoretical foundation to pursue their practice, through training teachers, in order to provide quality learning resources for their students.